2017
DOI: 10.1111/1467-8268.12238
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and Food Insecurity in Urban Ethiopia

Abstract: Although unemployment is often associated with food insecurity, the paths through which it leads to food insecurity is less explored. This study investigates the effects of unemployment on food insecurity based on data collected from 410 randomly selected households in Addis Ababa and the Munessa district of Arsi Zone. Binary logistic regression was used to analyze the data. The results show that 55.9 percent of the respondents were unemployed and only 12.4 percent of the households were food secure. The preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…That is, less poor households had a lower probability of being food insecure, while poorer households were more vulnerable to food insecurity during the pandemic. This result is also consistent with the a priori expectation of Harris‐Fry et al (2015), Etana and Tolossa (2017) and Abdullah et al (2019).…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…That is, less poor households had a lower probability of being food insecure, while poorer households were more vulnerable to food insecurity during the pandemic. This result is also consistent with the a priori expectation of Harris‐Fry et al (2015), Etana and Tolossa (2017) and Abdullah et al (2019).…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…This may explain the lower prevalence of food insecurity that we found in our study. This study has revealed that unemployment among the parents of adolescents was associated with food insecurity (Etana & Tolossa, 2017). Furthermore, this study has confirmed the outcomes of previous studies where low monthly incomes were associated with food insecurity (Norhasmah et al, 2011;Mohamadpour et al, 2012;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Studies of food expenditures have been conducted by some scholars, but the majority focuses on the composition of food consumed and its relationship with income [22,23], economic growth [24,25], as well as urbanization [5,[26][27][28][29][30][31][32]. In addition, other studies showed the relationship between food consumption composition with poverty [33][34][35] and unemployment [36][37][38][39][40] showing that both issues limit people's ability to consume more various and healthier food. It should be of concern that currently, the connection among regions has been increased extensively; thus, the flow of goods and people, including food products, has become more intense.…”
Section: Introductionmentioning
confidence: 99%